Ants on plants: a meta-analysis of the role of ants as plant biotic defenses - Rosumek, Felix B; Silveira, Fernando A. O; de S. Neves, Frederico; de U. Barbosa, Newton P; Diniz, Livia; Oki, Yumi; Pezzini, Flavia; Fernandes, G. Wilson; Cornelissen, Tatiana (Oecologia, 2009)
We reviewed the evidence on the role of ants as plant biotic defenses, by conducting meta-analyses for the effects of experimental removal of ants on plant herbivory and fitness with data pooled from 81 studies. Effects reviewed were plant herbivory, herbivore abundance, hemipteran abundance, predator abundance, plant biomass and reproduction in studies where ants were experimentally removed (n = 273 independent comparisons). Ant removal exhibited strong effects on herbivory rates, as plants without ants suffered almost twice as much damage and exhibited 50% more herbivores than plants with ants. Ants also influenced several parameters of plant fitness, as plants without ants suffered a reduction in biomass (-23.7%), leaf production (-51.8%), and reproduction (-24.3%). Effects were much stronger in tropical regions compared to temperate ones. Tropical plants suffered almost threefold higher herbivore damage than plants from temperate regions and exhibited three times more herbivores. Ant removal in tropical plants resulted in a decrease in plant fitness of about 59%, whereas in temperate plants this reduction was not statistically significant. Ant removal effects were also more important in obligate ant-plants (=myrmecophytes) compared to plants exhibiting facultative relationships with hemiptera or those plants with extrafloral nectaries and food bodies. When only tropical plants were considered and the strength of the association between ants and plants taken into account, plants with obligate association with ants exhibited almost four times higher herbivory compared to plants with facultative associations with ants, but similar reductions in plant reproduction. The removal of a single ant species increased plant herbivory by almost three times compared to the removal of several ant species. Altogether, these results suggest that ants do act as plant biotic defenses, but the effects of their presence are more pronounced in tropical systems, especially in myrmecophytic plants.